2020
DOI: 10.32539/sjm.v3i2.124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Rhinosinusitis in ENT Departement RSUP Dr. Mohammad Hoesin Palembang Period 2016-2018

Abstract: Chronic rhinosinusitis (CRS) is an inflammation involving the nose and paranasal sinuses where the patient has two or more major symptoms or one major symptom with two minor symptoms for ≥12 weeks. The prevalence of CRS throughout the world population is around 10-12%. The prevalence of CRS in Indonesia is uncertain. A research has been conducted on the prevalence of CRS in RSUP Dr. Mohammad Hoesin Palembang in 2015, therefore this study aims to find out more about the prevalence of CRS in the ENT Department o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…A study conducted at Dr. Mohammad Hoesin, Palembang found that the prevalence of CRS was higher in men compared to women with a ratio of 1.4:1. [11] In study conducted by Benjamin et al, prevalence of CRS found to be higher in women rather than men because of higher asthma comorbid in women. [12] This study also found no significance between age and CRS endotype.…”
Section: Discussionmentioning
confidence: 93%
“…A study conducted at Dr. Mohammad Hoesin, Palembang found that the prevalence of CRS was higher in men compared to women with a ratio of 1.4:1. [11] In study conducted by Benjamin et al, prevalence of CRS found to be higher in women rather than men because of higher asthma comorbid in women. [12] This study also found no significance between age and CRS endotype.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, Ravantara et al. 15 found that 65.7% of their patients with chronic sinusitis were men, with a male to female ratio of 1.9:1. Albeit, the National Health Interview Survey age-adjusted data found that sinusitis was more common in women (63%) than in men.…”
Section: Discussionmentioning
confidence: 94%
“…Chicken Egg 1 Indonesia found that the chief complaint in CRS was nasal blockage. [13,14] the 'cardinal' symptoms are nasal obstruction or congestion, nasal discharge (which can be anterior or posterior), alteration in sense of smell, facial pain, and pressure. Nasal obstruction and alteration of smell and taste are both the most severe and prevalent symptoms in CRSwNP, while in CRSsNP, nasal obstruction is again the most severe, with facial pain and nasal discharge reported as equally severe as altered smell and taste.…”
Section: Resultsmentioning
confidence: 99%